Surface area of the tip of the enterocytes in small intestine mucosa of broilers submitted to early feed restriction and supplemented with glutamine - Silva, A. V. Fischer da; Maiorka, A.; Borges, S. A.; Santin, E.; Boleli, I. C. [UNESP]; Macari, Marcos [UNESP] (My University, 2007)
A total of 640 one-day-old male Cobb chicks were used to evaluate the effects of early feed restriction and glutamine on villi density and tip surface of enterocytes in the small intestine of broilers. A two-factor factorial experimental design with glutamine and feed restriction as main factors was used. Treatments consisted of quantitative feed restriction at 30% of ad libitum intake from 7 to 14 days of age, and glutamine addition at 1% in the diet from 1 to 28 days of age. Sections of the small intestine (duodenum, jejunum, ileum) were collected at 14 and 21 days of age for analyses by scanning and transmission electron microscopy. Villi density decreased with age and increased in cranial-caudal direction. Glutamine increased villi density in the small intestine. Microvilli density and height decreased with age. Glutamine increased microvilli width. The jejunum was the segment with the largest surface area of the tip of the enterocytes, followed by the duodenum and the ileum. Feed restriction decreased the surface area of the tip of the enterocytes in the small intestine at 14 and at 21 days of age. Glutamine supplemented in the feed increased the surface area of the tip of the enterocytes of the jejunum and ileum at 21 days of age. © Asian Network for Scientific Information, 2007.
Keywords: Electron microscopy; Feed restriction; Glutamine; Intestinal mucosa; Microvilli amplification factor